NIGERIAN LOCAL GOVERNMENT ADMINISTRATION: A COMPARATIVE ANALYSIS OF THE THIRD AND FOURTH REPUBLICS - Towoju Adedoyin John; Mohammed Idris Danjuma; Ibrahim O Salawu (Malete Journal of Accounting and Finance)
Local governments are not independent unlike nation-states, which derives their existence and powers from the law enacted by a higher government. While they are constitutionally provided for as a third tier and independent level of government, like the other two; the Federal and State Governments in Nigeria. Local government in Nigeria is rooted on historical antecedents of reforms. The 1976 Local Government Reform in Nigeria and the subsequent one that followed were geared towards making local governments, the bedrock for socio-economic and political development. Somehow, the 1999 constitution of the fourth republic seems to have overridden the gains and aspirations of this tier of government, this assertion can be verified by looking at how the 1999 constitution undermined the autonomy and aspiration as well as the efficacy of grassroots governance, unlike the 1989 constitution of the third republic that gives more power to local governments. The major findings were that each reform measure was necessitated by the short-comings inherent in the preceding system; some of the reforms were far reaching and had positive impacts, while others were cosmetic in nature and mainly for political expediency. The paper recommends among other things the strengthening of local governments in the country, through granting of considerable autonomy, especially financial, political as well as administrative. Finally, the paper concludes that since the local government today remains the key institution in local governance, there is a need for another constitutional arrangement or reform in order to ensure autonomy of local governments politically and financially.